Ecological assessment of surface water quality of the Western Bug river in the border region of Ukraine and Poland - Kovalchuk, Ivan; Karaim, Olha; Dzham, Olena; Lavrynyuk, Zoryana; Karaim, Volodymyr (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2025)
The purpose of the work is to conduct an environmental assessment of the surface water quality of the Western Bug River within the border region of Ukraine and Poland.Methods. The study employed methods of generalization and systematization, analysis and synthesis, comparative, abstract-logical, and sequential approaches.Results. An analysis was conducted on the content of major pollutants at three observation points along the Western Bug River (1 – Zabužje village, border with the Republic of Poland; 2 – Ustyluh city, 500 m downstream from the confluence of the Luga River, border with the Republic of Poland; 3 – Ambukiv village, 500 m downstream from the confluence of the Khuchva River, border with the Republic of Poland) in 2021–2023. It was established that the concentration of most pollutants in the surface waters of the Western Bug River remained within the normative limits during the study period. Occasional exceedances were observed for suspended solids and phosphates across all observation points. In the first half of the study period, an excess of ammonium salt concentrations was noted, but a gradual decrease in this parameter was observed from 2021 to 2023. The concentration of nitrites remained within permissible limits at all observation points throughout the study period. According to the pollution index for salt composition components, the water quality of the Western Bug River improved over time. In Zabužje, it ranged from “satisfactory” (until February 2022) to “good” (until September 2023), while in Ustyluh, it remained consistently “good”. At the Ambukiv observation point, the water was classified as “good” with a “very good” category, remaining “clean” and “fairly clean” throughout the period. The tropho-saprobic index indicates slight pollution at all observation sites. The water was classified as “satisfactory” in terms of condition, while its purity ranged from “polluted” to “slightly polluted”. However, based on the index of specific toxic indicators, the water at all sites remained “good” to “very good” in condition and consistently “clean”. The comprehensive environmental index confirmed an overall “good” condition of surface waters at all sites from 2021 to 2023, with purity levels classified as “clean” and “fairly clean.” Based on the comprehensive environmental index, the surface waters of the Western Bug River in 2021–2023 at all three observation sites were characterized as “good” in terms of water quality class based on condition, “good” in terms of quality category based on condition, “clean” in terms of water purity class, and “fairly clean” in terms of purity category.Conclusions. The assessment of the ecological state of the Western Bug River from 2021 to 2023 indicates that its surface waters largely meet the normative quality standards. A gradual improvement in parameters, particularly a reduction in ammonium salt concentration, has been observed. According to the comprehensive environmental index, the waters at all three observation sites are characterized as “good” and “clean”.